Application of Decision Support System for the Best Teacher Selection with the Simple Additive Weighting Method - S Susliansyah; Fintri Indriyani; Annisa Dwi Wijayanti (IJISTECH (International Journal of Information System and Technology), 2020)
Selection of the best teachers at SMK is carried out once a month in order to provide motivation for teachers in teaching and learning activities, in decision making is still done manually and also subjectively. So that the results of the decisions are inaccurate and cause social jealousy among teachers. Therefore, in assessing the best teachers, a decision support system is needed to obtain accurate results. The Decision Support System method used for problem-solving in this study is the Simple Additive Weighting (SAW) method. The criteria used are present on time, responsibility, dress neatly and politely, participate and contribute, be active and productive, and help fellow teachers. The result of this research is to produce the selected alternative with the greatest value.